Spawning Period and Size at Maturity of Scaldback, Arnoglossus kessleri Schmidt, 1915 (Pleuronectiformes: Bothidae), Caught by Beam Trawl in The Black Sea, Turkey - Sabri BİLGİN; Hatice ONAY (Aquatic Sciences and Engineering, 2019)
The scaldback, Arnoglossus kessleri, is a small fish that belongs to the Bothidae family. This species is a demersal fish inhabiting sandy and muddy bottoms where it lives, generally buried in the sand. Even in Turkey, the biology of A. kessleri is unknown, and there are very few complete studies of the biology of this fish in the Mediterranean Sea, including the Aegean Sea and the Sea of Marmara. To describe the spawning period, size at maturity (Lm), and length at maximum yield per recruit (Lopt) of A. kessleri, and to assess the differences in these parameters from other populations, a total of 12 months samplings were conducted between December 2012 and November 2013 in the Black Sea. The monthly fluctuation of the GSI values showed that the spawning period was between June and September in the study area. The Lm was estimated as 5.76 cm for females and 6.03 cm for males. The Lopt was calculated from the empirical relationships between the Lopt and Lm, and it was determined as smaller than Lm for both sexes (Lopt = 5.55 cm for female and Lopt = 5.82 cm for male) and also the reproductive load, Lm/Lmax, of females was estimated as a bit (1.4%) larger than males. The results of this study were offered as biological input parameters regarded as a reference for the management of the Black Sea stocks of the scaldback species.